The effects of sugar application on the concentrations of anthocyanin and flavonol of 'mahajanaka' mango (mangifera indica linn. cv. mahajanaka) fruit - Lueangprasert K. (2014)
The relationship between contents of anthocyanin, flavonol, sugars and sunlight were explored in Mahajanaka mango (Mangifera indica Linn. cv. Mahajanaka) fruit exocarp in Thailand. Sugars including fructose (5 or 10% weight/volume; w/v) and sucrose (10% w/v) were applied three times at 77, 84 and 91 days after full bloom before red colour development. Anthocyanin and flavonol contents increased throughout fruit development, especially after the application of 10% fructose with a greater response in the sunny exposed sections of the fruit than in shaded sections. The concentrations of sucrose and fructose were generally higher in the exposed sections after applications of the sugars compared with the control. There was a positive correlation between anthocyanin and flavonol contents across the sugar treatment in the exposed side of the fruit. However, there were strong correlations between the concentrations of anthocyanin and sugars in the shaded side of the fruit. These results suggest a strong relationship between colour development, light and exposure to exogenous sugars in this mango cultivar.